A high-resolution, unified incompressible solver framework for turbulent flows in OpenFOAM - Teschner, Tom-Robin (Cranfield University, 2023)
This work introduces the Factional-Step, Artificial Compressibility with Pressure Projection (FSAC-PP) method into OpenFOAM, a fast pressure-velocity coupling algorithm for incompressible flows. It is tested for the lid driven cavity problem and it is shown that the pressure Poisson solver speeds up the solution by up to 27.1% compared to the Pimple algorithm available in OpenFOAM. Comparison against the Pressure Projection method from which the FSAC-PP method is derived, are similar favourably.
Keywords: incompressible flow; FSAC-PP; OpenFOAM